2006
DOI: 10.1111/j.1365-2478.2006.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing state‐of the art near‐surface models of a seismic test line from Saudi Arabia

Abstract: A B S T R A C TWe present a seismic Test Line, provided by Saudi Aramco for various research teams, to highlight a few major challenges in land data processing due to near-surface anomalies. We discuss state-of-the-art methods used to compensate for shallow distortions, including single-layer, multilayer, plus/minus, refraction and tomostatics methods. They are a starting point for the new technologies presented in other papers, all dealing with the same challenging data described here.The difficulties on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In any case, subsurface architecture mapping with the seismic reflection method requires a good-quality shallow-velocity structure for static correction performance. Detailed nearsurface models are usually obtained from high-density borehole information or velocity models derived from seismic tomography and/or first arrival inversions (Bridle et al, 2006;The study area of this work is located in Hontomin (Burgos, Spain). This site has been the target for oil exploration during the early 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, subsurface architecture mapping with the seismic reflection method requires a good-quality shallow-velocity structure for static correction performance. Detailed nearsurface models are usually obtained from high-density borehole information or velocity models derived from seismic tomography and/or first arrival inversions (Bridle et al, 2006;The study area of this work is located in Hontomin (Burgos, Spain). This site has been the target for oil exploration during the early 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D seismic field data under consideration is provided by Saudi Aramco. The description of the dataset and its geological settings are given by Bridle et al (2006). The data is taken from a 2D line in Saudi Arabia in an area characterized by rough topography and complex near-surface geology.…”
Section: Results For Field Datamentioning
confidence: 99%
“…Coherence inversion (Landa, Keydar and Kravtsov 1995) can yield useful results but is ineffective where coherent noise is present. Refraction traveltime inversion has previously been used to successfully model the near surface (Lanz, Maurer and Green 1998;Bergman, Tryggvason and Juhlin 2006;Zelt, Azaria and Levander 2006;Yordkayhun et al 2007) Bridle et al (2006) showed that it yields better results than the plus-minus method). Traveltime inversion models are quite efficient, often requiring only a few iterations to converge, and are less likely to include unnecessary subsurface features than forward modelling of the same data (White and Boland 1992).…”
Section: Prior Workmentioning
confidence: 97%